PSYCHOLOGICAL PERSONALITY OF THE MAIN CHARACTER IN JOHN GREEN’S THE FAULT IN OUR STARS - Nofriana Silaban; Trijuliman Giawa; Ismarini Hutabarat (LPPM Universitas Darma Agung, 2021)
This study deals with Psychological Personality of the Main Character in John Green’s The Fault in Our Stars. In analyzing the data, the writer applies two theoretical approaches, namely intrinsic and extrinsic approaches. In this thesis psychological discipline is applied to analyze personality in the novel. The Thesis applies qualitative descriptive where the focus of this analysis are to find out the kind of personality of the main character portrayed in John Green’s The Fault in Our Stars and the impact of the main character’s personality change. The result of this analysis shows that there are 4 (four) types of personality, they are Introvert Thinking Type, Introvert Feeling Type, Introvert Sensing Type, Introvert Intuiting Type which are possessed by the main character.